2014
DOI: 10.1186/s13041-014-0063-0
|View full text |Cite
|
Sign up to set email alerts
|

Human primary mixed brain cultures: preparation, differentiation, characterization and application to neuroscience research

Abstract: BackgroundCulturing primary cortical neurons is an essential neuroscience technique. However, most cultures are derived from rodent brains and standard protocols for human brain cultures are sparse. Herein, we describe preparation, maintenance and major characteristics of a primary human mixed brain culture, including neurons, obtained from legally aborted fetal brain tissue. This approach employs standard materials and techniques used in the preparation of rodent neuron cultures, with critical modifications.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 31 publications
(30 reference statements)
1
40
0
Order By: Relevance
“…These cells were generally seen has having an empty or hollow area in the cell due to lack of staining in this region. These cells were counted using the count feature in Adobe Photoshop (Ray et al, 2014). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These cells were generally seen has having an empty or hollow area in the cell due to lack of staining in this region. These cells were counted using the count feature in Adobe Photoshop (Ray et al, 2014). …”
Section: Methodsmentioning
confidence: 99%
“…Protein standard (BioRad #161–0374) was loaded in one lane of the gel as a marker. Human fetal neuron (HFN) lysate (Ray et al, 2014) and human brain lysate (Long et al, 2014) were also loaded as positive controls for p-ERK expression. Gel was run at 200 V for 1.5 h, and transfer was performed using the Invitrogen iBlot system.…”
Section: Methodsmentioning
confidence: 99%
“…Abundant tau and amyloid-β production in human brain cultures provides a powerful cellular model for AD. In a recent study Ray et al provide a well-characterized methodology for fetal human primary brain cell culture, which is useful to test the therapeutic efficacy of drugs targeting AD [28]. Cultures of induced pluripotent stem cell (iPSC) generated from fibroblasts of FAD patients with presenilin 1 and presenilin 2 mutations were characterized after acquiring neuronal lineage [29].…”
Section: Cell Type Considerations For Disease Modifying Therapiesmentioning
confidence: 99%
“…Some papers presented morphological and molecular characteristics of NSPC derived from the forebrain of human fetuses on gestation weeks 7-12, which corresponds to the period of active cortical neurogenesis [3,4,31,33], while generation of neurons in human neocortex during the second trimester decreases [25]. Morphological studies showed that this period is characterized by migration and differentiation of neurons, increase in cell mass, and structural changes [8,25] determining specifi c properties of human brain cortex that distinguish it from the brain cortex of animals [35].…”
mentioning
confidence: 99%
“…In humans, active neurogenesis in the neocortex lasts 65 days, from day 50 (week 7) through day 115 (week 17) of fetal development [2] and signifi cantly decreased by gestation weeks 18-24 [25,35]. NSPC populations in humans and rodents differ by cell composition [16] during in vivo and in vitro differentiation [7,13,17,24,33]. All these differences indicate the necessity of using human fetal neural cells as the positive control during the development of advanced methods of clinical cell therapy of neural disorders in humans based on embryonic or induced pluripotent stem cells [27].…”
mentioning
confidence: 99%